Conjugal multiple system atrophy: Chance, shared risk factors, or evidence of transmissibility?. (October 2019) - Coon, Elizabeth A.; Rocca, Walter; Melson, Christopher S.; Ahlskog, J. Eric; Matsumoto, Joseph Y.; Low, Philip A.; Singer, Wolfgang
Abstract: Objective: To describe conjugal multiple system atrophy (MSA) in a couple married for 44 years, and to report environmental risk factors possibly contributing to the occurrence. Methods: Case description of conjugal MSA with report of shared environmental risk factors and retrospective review of consecutively diagnosed MSA patients between 1998 and 2012 with autonomic reflex screen at Mayo Clinic, Rochester (clinical series). Probability calculation was based on the age-specific point prevalence of MSA. Results: A husband and wife both developed MSA symptoms at age 63. The husband's onset was of imbalance, followed by falls and genitourinary failure; parkinsonism and antecollis was evident on examination. Autonomic testing showed widespread autonomic failure. The patient died 2.25 years after onset. The wife initially developed urinary symptoms progressing to incontinence. Parkinsonism, dysphonia, and falls began within 1 year. Autonomic testing revealed severe autonomic failure. Interview with the surviving wife and son revealed substantial chemical exposure, in particular pesticides. In our clinical series, there were no other cases of conjugal MSA. Assuming an age-specific point prevalence of MSA based on population studies and independence of the two events, the probability of both individuals developing MSA by chance is 6.08 e−9. Conclusion: Based on the population point prevalence of MSA, conjugal MSA is rare but possible. We conclude that this case of conjugal MSA likely occurred by chance; however, exposure to shared risk factors (pesticides) may be contributory. Because this is the first reported case of conjugal MSA, to our best knowledge, evidence for transmissibility between spouses is lacking. Highlights: We report conjugal MSA where both husband and wife developed MSA-parkinsonism. Assuming an age-specific point prevalence of MSA and independence of the two events, conjugal MSA may occur by chance. Exposure to shared risk factors may contribute to MSA in spousal pairs rather than offer evidence for transmissibility.